Mesenchymal stem cells derived from hPSC via neural crest attenuate chemotherapy-induced premature ovarian insufficiency by ameliorating apoptosis and oxidative stress in granulosa cells - Xinran Li; Jinrong Liao; Youhong Zheng; Wei Cai; Jie Chen; Yu Liang; Yuanmei Chen; Xiaoxuan Li; Jiamao Luo; Jiaxin Xie; Manping Zhou; Lilin Hang; et al. (Stem Cell Research & Therapy)
Abstract Background Premature ovarian insufficiency (POI) poses a significant threat to female reproductive health and currently lacks effective interventions. Recent studies highlight the promising potential of human pluripotent stem cell-derived mesenchymal stem cells (hPSC-MSC) in regenerative medicine. However, research on hPSC-MSC-based treatments for POI remains limited, particularly in the characterization of the intermediate differentiation stages from hPSC to MSC. This study presents an accelerated differentiation protocol for generating hPSC-MSC via neural crest cells (NCC) and evaluates their therapeutic potential in chemotherapy-induced POI. Methods We modified a canonical small molecule-mediated protocol for hPSC-NCC-MSC differentiation. Systematic characterization of differentiated-cells was performed using qPCR, immunofluorescence, cell viability assays, flow cytometry and trilineage differentiation. In vivo, hPSC-NCC-MSC were transplanted into chemotherapy-induced POI SD rat models, and parameters such as body weight, ovarian weight, estrous cycle, hormone levels, follicle count, and mating were assessed. Granulosa cells (GC) apoptosis was analyzed using TUNEL assay and immunohistochemistry. In vitro, their effects on apoptosis inhibition and oxidative stress alleviation were investigated in a cultured GC cell line. Additionally, comparisons between umbilical cord MSC (UC-MSC) and hPSC-NCC-MSC in chemotherapy-induced POI was conducted. Results Our optimized protocol, combining CHIR99021 and SB431542, efficiently induced NCC from both human embryonic stem cells (hESC) and human induced pluripotent stem cells (hiPSC). The programmed hPSC-NCC-MSC, characterized by specific NCC markers (P75, HNK1, SOX10, and AP2α), exhibited typical MSC morphology, trilineage differentiation potential, favorable cell viability, and prominent anti-senescence properties. Among these, NCC differentiated from H1-hESCs (H1-NCC) demonstrated the highest induction efficiency (72.45%), and H1-NCC-derived MSC (H1-NCC-MSC) displayed superior proliferation and anti-senescence properties compared to UC-MSC. Besides, H1-NCC-MSC exhibited therapeutic efficacy comparable to UC-MSC in both in vivo and in vitro models of chemotherapy-induced POI, potentially through mechanisms involving reduced GC apoptosis, alleviated oxidative stress, and improved mitochondrial function. Conclusions Our findings propose a modified hPSC-NCC-MSC differentiation protocol, offering an inexhaustible and stable source for regenerative therapies. Furthermore, we provide the first experimental evidence that hPSC-NCC-MSC have therapeutic potential comparable to UC-MSC in restoring chemotherapy-induced POI. The underlying mechanisms are likely associated with paracrine-mediated effects on GC apoptosis, oxidative stress, and mitochondrial dysfunction.